The effect of pressure on friction of steel and ice and implementation to bobsleigh runners - Dumm, M.; Hainzlmaier, C.; Boerboom, S.; Wintermantel, E. (The Engineering of Sport 6, Volume 3 Developments for Innovation, 2006)
Bobsleigh runners are a critical factor for success in bobsleigh races. It is very important to use runners which generate a minimum frictional loss in contact with ice. As other studies show, the pressure greatly influences the coefficient of friction between steel and ice. In literature, there are indications for a decreasing coefficient of friction with increasing pressure as well as for an increasing coefficient of friction. This paper presents a method to measure the coefficient of friction ? between steel and ice. The normal pressure p on the sample was increased continuously. It was shown, that there is a minimum coefficient of friction for an optimum pressure value popt. Results were transferred to bobsleigh engineering. A molding method was developed to examine the surface of the ice, in particular the trace a runner generates in the bobsleigh track. A highly precise impression material was used and impressions were analyzed by scanning electron microscopy (SEM). The actual pressure between runner and ice was estimated according to SEM analysis. Comparing the actual pressure with laboratory results, design recommendations for a new bobsleigh runner were determined.